The Electorate in Poland’s Large and Medium-Sized cities and Towns and its Influence on the Results of the 2007 Parliamentary Elections - Matykowski, Roman (Bulletin of Geography. Socio-economic Series, 2010)
Urbanization is regarded among the most significant factors affecting election-related behaviour in Poland. In order to identify the importance of Poland’s municipal electorate, a procedure of reverse elimination was applied to the electorates of successive largest cities in Poland, followed by a structure of supporting the strongest political parties at each stage of the cities’ rank elimination. Whenever each successive elimination is followed by dwindling support for a given party, this party is referred to as pro-metropolitan.